1975
DOI: 10.3382/ps.0540591
|View full text |Cite
|
Sign up to set email alerts
|

Nonprotein Nitrogen for Growing Chickens

Abstract: Diammonium citrate (DAC) and urea were not used beneficially as nitrogen sources in the diet of young chicks. Supplementation of 0.43% urea to a low-protein practical diet did not significantly affect gain or feed efficiency. Adding 2.85% or 5.70% DAC to a low-protein basal depressed growth and feed efficiency significantly. Percentages of nitrogen intake absorbed and retained by chicks were depressed by DAC. When diets were balanced by added amino acids. DAC did not depress weight gains, but nitrogen percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…However, Trakulchang and Balloun (1975) reported a decrease in egg production with an increase in the level of dried poultry droppings. Adverse effects of dietary dried poultry manure, in terms of reduced egg weight and feed efficiency, were reported by Biely et al (1972).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, Trakulchang and Balloun (1975) reported a decrease in egg production with an increase in the level of dried poultry droppings. Adverse effects of dietary dried poultry manure, in terms of reduced egg weight and feed efficiency, were reported by Biely et al (1972).…”
Section: Introductionmentioning
confidence: 92%
“…Yet, Trakulchang and Balloun (1975) found that a 15% protein diet supplemented with dried poultry droppings and amino acids decreased the weight gain and feed efficiency of broiler chicks and of eight-monthold layers. Sloan and Harms (1973) indicated that depression of growth rate due to feeding dried poultry droppings might be due to a depression in caloric intake of the birds.…”
Section: Introductionmentioning
confidence: 95%
“…If the basal diet had been formulated to contain a lower protein level, the effects of supplemental intact protein and NPN sources may have been more pronounced. In fact, many investigators used lower protein in practical or purified diets in their NPN utilization studies with growing chicks (Moran et al, 1967;Lee and Blair, 1972;Allen and Baker, 1974;Trakulchang and Balloun, 1975). Sugar beet molasses generally failed to increase die utilization of NPN sources by laying hens or growing chicks, so the possibility that the sucrose moeity of sugar beet molasses might serve as a more readily available source of alpha-keto acid formation for the utilization of NPN compounds is not indicated by the data.…”
Section: Discussionmentioning
confidence: 62%
“…Ackerson et al (1940) fed growing chicks a diet in which 13% of protein nitrogen was supplied by urea and could find no beneficial effects. In subsequent reports a number of other investigators concluded that urea and diammonium citrate (DAC) could not be utilized by growing chicks (Jones and Combs, 1953;Moran et al, 1967;Reid, 1967;Bornstein and Lipstein, 1968;Trakulchang and Balloun, 1975;Kagan and Balloun, 1976). In contrast, a number of other researchers reported that urea and DAC could be utilized by growing chicks for growth.…”
Section: Introductionmentioning
confidence: 86%
“…They found that the efficiency of utilization of diammonium citrate was about 70-90% of that of L-glutamic acid but diammonium phosphate and urea were utilized with an efficiency of less than 40% of L-glutamic acid. However, Trakulchang and Balloun (1975) reported that supplementing a low-protein practical diet with 0.43% urea did not significantly affect body weight gain or feed efficiency of growing chickens. But, Okumura et al (1976) observed that the germ-free chicks did not benefit from urea supplement whereas the conventional birds showed better feed conversion efficiency and growth.…”
Section: Introductionmentioning
confidence: 96%